Surgical Roles in the Management of Metachronus Para-aortic Lymph Node Recurrence and Synchronous Para-aortic Lymph Node Metastasis in Colorectal Cancer Patients - Abd-Elaziz, Osama; Ali, Ramadan M.; Amin, Mohamed Farouk; Fahmy, Ahmed M.; Elshorbagy, Shereen; Mandour, Doaa; Hemeda, Rehab; Harb, Ola A.; Samir, Amr; El-Hendawy, Elsayed I. (Journal of Coloproctology, 2022)
Background The relative rarity of synchronous para-aortic lymph node (PALN) metastasis (SPM) and metachronous PALN recurrence (MPR) in colorectal carcinoma (CRC) patients leads to a limited number of studies on patient management, and no treatment guidelines have been established to date.Objective To assess the prognostic, predictive roles, and long-term outcomes of different management strategies for isolated MPR and SPM in CRC patients to establish the best one.Materials and Methods We included 35 CRC patients with isolated MPR and 25 patients with isolated SPM who underwent curative R0 resection. We performed PALN dissection (PALND) in 15 cases in MPR group and in 10 cases in the SPM group; all remaining patients in both groups underwent chemoradiotherapy (CRT) without further surgical intervention. During the study period of about 5 years, we compared the patients who underwent PALND and those who underwent CRT.Results The overall survival and recurrence-free survival rates were significantly longer in patients who underwent PALND (p = 0.049 and 0.036 respectively).Conclusions We showed that PALND in cases of CRC patients with SPM and MPR previously submitted to R0 resection was associated with favorable outcomes and better patient survival.
Keywords: colorectal cancer; metachronous para-aortic lymph node recurrence; synchronous para-aortic lymph node metastasis; surgery